Occurrence of hepatitis B and C virus infection in socioeconomic population strata from Recife, Pernambuco, Northeast Brazil - Carolline de Araújo Mariz; Cynthia Braga; Maria de Fátima Pessoa Militão de Albuquerque; Carlos Feitosa Luna; Daniela Medeiros Salustiano; Naishe Matos Freire; Clarice Neuenschwander Lins de Morais; Edmundo Pessoa Lopes (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2024)
ABSTRACT Objective: To estimate the probability of infection with hepatitis B (HBV) and C (HCV) viruses in different socioeconomic strata of the population of Recife, Northeast Brazil. Methods: Study carried out from samples obtained in a survey of residents of a large urban center that had a population base and stratified sampling with random selection of households using the "Brazil Sample" package in the R software. HBV (HBsAg) and anti-HCV was performed using immunochromatographic tests. In cases positive for HBsAg, anti-HBc and HBeAg were tested using chemiluminescence, as well as HBV-DNA using real-time PCR. For cases positive for anti-HCV, the search for this antibody was repeated by chemiluminescence and for HCV-RNA by real-time PCR. The occurrence of HBsAg and anti-HCV cases in the general population was estimated based on a theoretical negative binomial distribution. Results: Among 2,070 samples examined, 5 (0.24%) were HBsAg and 2 (0.1%) anti-HCV positive. The majority of cases had self-reported skin color as black/brown (6/7), education level up to high school (6/7), a steady partner (5/7) and lived in an area of low socioeconomic status (5/7). Conclusion : The occurrence of HBsAg and anti-HCV was lower than those previously found in population-based studies and slightly lower than the most recent estimates. Individuals with lower socioeconomic status should be a priority target of public health policies.